1989
DOI: 10.1111/j.1399-3054.1989.tb04647.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status of the potato tuber and Ca2+ deficiency as a physiological stress

Abstract: The antioxidant status of potato (Solanum tuberosum L.) tubers of two genotypes, cv. Désirée and clone 10337de40 was investigated in relation to susceptibility to internal rust spot (IRS), a Ca2+‐related physiological disorder. Concentrations of total calcium within the perimedulla tissue of tubers, grown with a restricted (1 mM CaCl2) Ca2+ supply, were similar in cv. Désirée (IRS resistant) and clone 10337de40 (IRS susceptible). A range of antioxidants was assayed in order to assess antioxidant status in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It is now known that activated oxygen species are generally produced in high amounts in plants subjected to different environmental stresses such as high and low temperatures, water deficit, high light intensity, herbicide treatment, or mineral nutrient deficiency, and these activated species cause a severe oxidative damage (Dhindsa and Matowe, 1981;Wise and Naylor, 1987;Monk and Davies, 1989;Cakmak and Marschner, 1990;. It has been widely reported that plants possessing high concentrations of antioxidants have high resistance to the oxidative damage caused by the activated oxygen species (Wise and Naylor, 1987;Spychalla and Desborough, 1990).…”
Section: B Antioxidant Response Of Cotton To Salt Stressmentioning
confidence: 99%
“…It is now known that activated oxygen species are generally produced in high amounts in plants subjected to different environmental stresses such as high and low temperatures, water deficit, high light intensity, herbicide treatment, or mineral nutrient deficiency, and these activated species cause a severe oxidative damage (Dhindsa and Matowe, 1981;Wise and Naylor, 1987;Monk and Davies, 1989;Cakmak and Marschner, 1990;. It has been widely reported that plants possessing high concentrations of antioxidants have high resistance to the oxidative damage caused by the activated oxygen species (Wise and Naylor, 1987;Spychalla and Desborough, 1990).…”
Section: B Antioxidant Response Of Cotton To Salt Stressmentioning
confidence: 99%
“…When plants are subjected to environmental stress, the balance between the production of reactive O, species and the quenching activity of antioxidants is upset, often resulting in oxidative damage (Harper and Harvey, 1978;Dhindsa and Matowe, 1981;Rabinowitch and Fridovich, 1983;Wise and Naylor, 1987;Monk and Davies, 1989;Spychalla and Desborough, 1990;Cakmak and Marschner, 1992;Polle et al, 1992;Asada, 1994;Krause, 1994). Plants with high levels of antioxidants, either constitutive or induced, have been reported to have a greater resistance to this oxidative damage (Harper and Harvey, 1978;Dhindsa and Matowe, 1981;Wise and Naylor, 1987;Monk and Davies, 1989;Spychalla and Desborough, 1990;Mandamanchi and Alscher, 1991;Polle and Rennenberg, 1994).…”
mentioning
confidence: 99%
“…Plants with high levels of antioxidants, either constitutive or induced, have been reported to have a greater resistance to this oxidative damage (Harper and Harvey, 1978;Dhindsa and Matowe, 1981;Wise and Naylor, 1987;Monk and Davies, 1989;Spychalla and Desborough, 1990;Mandamanchi and Alscher, 1991;Polle and Rennenberg, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This can upset the balance of oxygen free radical production and quenching, and tests the antioxidant capacity of the aerobic cell (3,4,7,13,21,24,26,30). High constitutive levels or high induced levels of antioxidants in a plant cell may provide resistance to a particular stress (6,15,30).…”
mentioning
confidence: 99%